Sphalerite as a non-traditional critical metal source: Correlative microscopy (EPMA, EBSD, and APT) of cobalt-enriched sulfides from the sediment-hosted copper-cobalt Dolostone Ore Formation deposit, Namibia - Bertrandsson Erlandsson, Viktor; Gopon, Phillip; Waldl, Helene; Misch, David; Ellmies, Rainer; Melcher, Frank (Frontiers in Earth Science, 2023)
Sphalerite from the sediment-hosted Dolostone Ore Formation (DOF) Cu-Co-Zn deposit, in northwestern Namibia, has previously been shown to contain extremely high concentrations of the critical metal Co (up to 1 wt%). These concentrations are the highest reported in sphalerite to date, and the how and why of sphalerite being able to incorporate such high concentrations of Co are poorly constrained. We use correlative electron microprobe microanalysis, electron backscattered diffraction, and atom probe, to reconstruct the likely incorporation mechanisms and modes of occurrence of such high Co concentrations in natural sphalerite. While over twenty samples were studied, the comprehensive analytical workflow was executed on one representative sample to gain a detailed understanding of Co enrichment. The sulfides of the studied sample are: Co-rich pyrite, chalcopyrite, Co-rich sphalerite, linnaeite, cobaltpentlandite, and cobaltite, mentioned in order of abundance. Detailed petrography of these sulfides indicates that they formed through three stages during the main Cu-Co-Zn ore stage of the DOF. Cobalt was initially contained in pyrite that grew during Ore Stage 1 and was later affected by oxidizing fluids (Ore Stage 2). This led to remobilization and growth of linnaeite (Co2+Co3+2S4). A later change in fO2 (Ore Stage 3) led to the breakdown of linnaeite and the further growth of accessory cobaltite along with the Co-rich sphalerite and chalcopyrite. The hyper-enriched Co-sphalerite then is the last major sink for Co in the DOF deposit. A low Fe and Co, and high Zn sub-grain boundary network within the Co-rich sphalerite was identified by EPMA and EBSD. This sub-grain network is believed to have formed during a later, secondary metamorphic stage (Cu-Zn(-Pb) Ore Stage 4), which developed during ductile deformational mineralization styles such as pressure shadows and veins. Our APT data reconstructions show no evidence for Co-inclusions within the Co-sphalerite and spatial ion correlation analyses of the data suggest that Co occurs in the sphalerite through simple substitution of Zn. This study demonstrates that sphalerite may contain significant concentrations of the Co through simple substitution, potentially representing an important non-traditional Co source in future critical metal exploration.